The Role of Advertising in Motivating Consumer Preference for Selection of Tourism Destination - Nodirbek Ibrokhimov (International Journal on Orange Technologies, 2022)
'Travel for recreational, leisure, familial, or business reasons, usually for a short length of time,' is how tourism is defined. Tourism is typically associated with overseas travel, but it can also refer to domestic travel.' Tourism, in today's terminology, is a type of global link between nations and tourists from all over the world, presenting them to diverse cultures and societies, as well as their history, ancient, historical sites, and languages. As a result, in this ever-expanding global market, advertising has become a crucial instrument. Tourism's growth and development are crucial because it is such an integral part of any country's economic infrastructure. Advertising is an important tool for increasing tourism in a country by portraying the country's historical and cultural attractions in an appealing manner. Advertising is crucial to the evolution of this industry, as it provides economic growth, direct and indirect jobs, and, most importantly, a creative and competitive competition in the national and international travel industry. Importantly, in order to attain these goals, Travel Agencies and Ministry of Tourism and Business departments must work together. This graduation project investigates the impact of various tourism-related media and advertising strategies, assisting in the selection of the most effective tool for growing the country's tourism industry. The most effective promotional strategies for luring domestic and international passengers were handbooks, internet advertising, television, brochures, and newspapers, according to the conclusions of this study.